A variant NS1 protein from H5N2 avian influenza virus suppresses PKR activation and promotes replication and virulence in mammals. Issue 1 (31st December 2022) - Chung, Yun-Ting; Kuan, Chih-Ying; Liao, Guan-Ru; Albrecht, Randy A.; Tseng, Yeu-Yang; Hsu, Yu-Chen; Ou, Shan-Chia; Hsu, Wei-Li
ABSTRACT: Highly pathogenic avian influenza viruses (HPAIVs) frequently receive global attention as threats to public health. The NS1 protein is a key virulence factor known to impair host antiviral responses. The study herein revealed HPAIV H5N2 NS gene encoded additional protein; a truncated NS1 variant, designated NS3, produced by alternative splicing of the NS transcript. To examine the function of NS3 during infection, we generated recombinant viruses expressing either full-length NS1 (RG-AIV-T375G) or NS3 (RG-AIV-NS3). Interestingly, RG-AIV-NS3 virus produced higher titres than RG-AIV-T375G in multiple mammalian cell lines. However, RG-AIV-T375G exhibited a replication advantage over RG-AIV-NS3 in chicken DF-1 cells, indicating that host cell identity dictates the effect of NS3 on viral replication. In mice and mammalian cells, RG-AIV-NS3 infection elicited higher level of cytokines, including IFN-β, MX and TNF-α, potentially due to its higher replication activity. Based on mini-genome assay, NS3 had pronounced effects on viral replication machinery. Surprisingly, NS3 retained an interaction with PKR and suppressed PKR activation despite its lack of amino-acid residues 126-167. The poor replication ability of RG-AIV-T375G was partially restored in cells deficient in PKR suggesting that full-length NS1 may be insufficient to suppress PKR function. Notably, virulence of the full-length NS1-expressing RG-AIV-T375G virus was highly attenuated in mice when compared to RG-AIV-NS3. In summary, our study reveals the existence and function of a previously unidentified H5N2 viral protein, NS3. We found that NS3 is functionally distinct from NS1 protein, as it enhances viral replication and pathogenicity in mammalian systems, potentially via suppression of PKR activity.